Diseño de una ruta turística entre las parroquias de Isinliví y Chugchilán, pertenecientes al cantón Sigchos, provincia de Cotopaxi - Toaquiza Ante, Luis Mauro (2017)
At the research Project that was made in Cotopaxi, Sigchos canton, Insilivi parish, Chugchilán has a biodiversity of natural and cultural resources where touristic activities can be applied. For that reason, the research is focused to stablish in a right and sustainable way all the resources through the creation of a route which will show the touristic places. First, a descriptive analysis was made, using the method of Carla Ricaurte which lets getting primary and secondary information. Inhabitants in this place realize the next following activities: farming, breeding of animals and merchandise. Secondly, based on the methodology of the Ministerio of Turismo an inventory with all the touristic attractions was made in which a result of six natural places was got, these are: “Kunuk Yaku” thermal waters, “Chacaná” waterfall, “Yana Rumi” mountain, “El tilinti” lake, “Toachi” river, “ Quilotoa” green lagoon. Finally, was made a registration of flora and fauna from all this sector, also was made a quiz about what tourists are looking for, this took place at Quilotoa lagoon in which national and foreign tourists were evaluated. In fact, after the quiz it was possible to identify that the tourist profile is linked with the people, environmental, and cultural ambit. According to this information, it is possible to develop activities as trekking, cavalcade, cycling, climbing, and bird watching. Finally, using the MINTUR method a third phase was developed, in which the next following things must be included to the route: wood signs, pictograms. All these will push the attraction of the place, having as goal to improve the touristic infrastructure of the parish.